Análisis económico y social del programa de alimentación escolar (PAE) en instituciones fiscales del cantón Quevedo del gobierno del Econ. Rafael Correa Delgado período 2012 - Paredes Anchundia, Joffre Fabián (2014)
In Latin America in recent years have sought alliances and tools to fight the various economic and social problems of the nations of the region, in these partnerships is the joint work with the UN to agree to the MDGs (goals millennium), have been seen as a priority to combat hunger and child malnutrition. Since this leads to economic and social cost Ecuador was the need to create the PAE (SFP) which had its beginnings in the nineties in view of improving social development policies of the national government, yet between 2000 and 2005 Ecuador destination around 6% of GDP to social spending, with an average of 43.5 in education and 18% for health, which in those years 62% of total social spending. (PAE 2007) Within the canton, PAE through the Ministry of Education and with the coordination of the School Food Secretary in 2012 covered a total of 99 schools and approximately 25,000 students benefited directly. (SECRETARY OF SCHOOL FEEDING) This applied research is intended simply to point out the benefits of school feeding program "PAE" for students of tax in schools and therefore families, most considered low income and the effect generated the school feeding program in economic and social part of the favored. Find as a result that approximately 50% of the population of the canton receive income of less than $ 400 by placing them in a medium low, a quarter is below $ 318 (SBU) and a little more room population perceive corresponding revenue the upper middle class. This benefit to participating families SAP generates some savings which is perceived by more than quarter of the population who have children in public schools which receive the PAE.